Intra-operative augmented reality in distal locking - Londei, Roberto; Esposito, Marco; Diotte, Benoit; Weidert, Simon; Euler, Ekkehard; Thaller, Peter; Navab, Nassir; Fallavollita, Pascal (International Journal of Computer Assisted Radiology and Surgery, 2015)
Purpose: To design an augmented reality solution that assists surgeons during the distal locking of intramedullary nailing procedures. Method: Traditionally, the procedure is performed under X-ray guidance and requires a significant amount of time and radiation exposure. To absolve these complications, we propose video guidance that allows surgeons to achieve both the down-the-beam position of the intramedullary nail and its subsequent locking. For the down-the-beam position, the IM nail pose in X-ray is calculated using a 2D/3D registration scheme and later related to the patient leg pose which is calculated using video-tracked AR markers. For the distal locking, surgeons use an augmented radiolucent drill in which its tip position is detected and tracked in real-time under video guidance. Validation: To evaluate the feasibility of our solution, we performed a preclinical study on dry bone phantom with the participation of four clinicians. Results: Participants achieved 100 % success rate in the down-the beam positioning and 93 % success rate in distal locking using only two X-ray images in 100 s. Conclusions: We confirmed that intra-operative navigation using augmented reality provides an alternative way to perform distal locking in a safe and timely manner.
CRIS-Team Scopus Importer:2023-03-08
Keywords: C-arm fluoroscopy; Distal locking; Medical augmented reality; Orthopedic surgery; Video guidance